Patient experience and burden of haemolytic disease of the foetus and newborn: a systematic review - P. Maurice; J. McCallion; M. Fitzgibbon; J. N. Barthelmes; W. Karmous; E. J. Hardy; S. A. Mitchell; C. R. Mitchell; J. Lee; W. Noel; Andras Borsi; J. M. Jouannic (BMC Pregnancy and Childbirth)
Abstract Background Haemolytic disease of the foetus and newborn (HDFN) is an immune disorder driven by maternal alloimmunisation against foetal/newborn red blood cell antigens. HDFN can cause significant morbidity and mortality, with symptoms in the foetus ranging from mild anaemia to hydrops fetalis. While in newborns, HDFN can lead to severe forms of neonatal hyperbilirubinaemia and kernicterus. This systematic review (SR) aimed to identify and summarise real-world evidence (RWE) related to the patient burden/experience and economic burden of HDFN. Methods Electronic database searches supplemented by handsearching of grey literature, were conducted to identify studies that reported the clinical patient burden/experience, and economic burden of HDFN in Europe, the Middle East, and Africa (EMEA). Data from eligible studies were summarised in a narrative synthesis due to heterogeneity between studies. Results A total of 26 relevant publications were identified for inclusion in the SR, consisting of one study that directly measured Health Related Quality of Life, 9 studies reporting on proxy outcomes for patient burden and 18 studies reporting on economic burden (this includes two double-counted studies reporting more than one outcome type). Neurodevelopment, academic development, behaviour and personality were assessed as proxy outcomes for patient burden given the limited identification of patient-reported outcome data. These studies suggested potential neurodevelopmental impairments in children with HDFN. Despite these indirect insights into patient burden, identified data were limited and results should be interpreted with consideration of the inherent heterogeneity in design and endpoints assessed across RWE studies. Economic burden data were primarily limited to healthcare resource use outcomes, with limited reported data on healthcare costs, it is difficult to draw notable conclusions on the true economic burden of HDFN. Conclusions The current SR provides a clear summary of the available evidence for the patient experience and economic burden of HDFN. While the limited evidence indicates that HDFN does confer a significant burden on patients, the review identifies the need for further well-powered and representative observational studies using well-defined outcome measures to aid a greater understanding of the burden and experience of HDFN. Trial registration The protocol for this systematic review was registered in PROSPERO CRD42022328444.